PENGARUH AKTIVITAS NEGATIF TERHADAP PERILAKU INTERAKSI SOSIAL SD NEMBOL 2 KECAMATAN MANDALAWANGI - Hanafiah; Ahmad Rifai; Suci Dwi Handayani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2025)
The phenomenon of negative activities in elementary schools has become a real problem as social and technological developments influence student behavior. Activities such as unhealthy communication and other deviant behavior are often considered normal, yet they impact the development of children's social interactions. This study aims to analyze the influence of negative activities and examine how negatively they affect children. The background to this problem is based on concerns about the increasing negative behavior that can hinder students' ability to socialize and build positive relationships with peers. This study used a quantitative approach with a correlation study method. The subjects were 30 students at Nembol 2 Elementary School, Mandalawangi District, Pandeglang Regency. Data were collected using a questionnaire that measured the level of negative activities and students' social interaction behavior. The results of the regression analysis showed a significant and negative relationship between negative activities and students' social interaction behavior (r = -0.545, p = 0.002). This finding indicates that the higher the level of negative activities, the lower their social interaction behavior. Thus, the regression analysis indicates a significant and negative relationship between negative activities and students' social interactions. So basically, it's clear that bad things mess up how well students get along socially.